2013
DOI: 10.1371/journal.pone.0072733
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity of the Leaf Extract Obtained from Arrabidaea chica Cultivated in Southern Brazil

Abstract: Arrabidaea chica leaf extract has been used by people as an anti-inflammatory and astringent agent as well as a remedy for intestinal colic, diarrhea, leucorrhea, anemia, and leukemia. A. chica is known to be a good producer of phenolics. Therefore, in the present study, we investigated its antioxidant activity. The phenolic composition of A. chica leaves was studied by liquid chromatography coupled to diode array detection (LC–DAD) and liquid chromatography coupled to electrospray ionization-tandem mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 45 publications
(44 reference statements)
3
56
0
3
Order By: Relevance
“…during the tendon healing process. 4 Antimicrobial, 5 antiinflammatory, 6 and antioxidant 7 potentials of this species have also been reported.…”
Section: Introductionmentioning
confidence: 76%
“…during the tendon healing process. 4 Antimicrobial, 5 antiinflammatory, 6 and antioxidant 7 potentials of this species have also been reported.…”
Section: Introductionmentioning
confidence: 76%
“…Phenolics and flavonoids are secondary metabolites derived from tyrosine and phenylalanine with potent antibacterial and antioxidant activities [34]. It was reported that isolated flavonoids quercimeritrin ( 1 ), scutellarein ( 2 ), and rutin ( 3 ) have significant antioxidant activities against oxidative stress [3537]. Note that all three have 1,2-dihydroxybenzene groups which are readily oxidized to orthoquinones, making them strong antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, isoscutellarein, 6-hydroxyluteolin, hispidulin, scutellarein luteolin, and apigenin have been reported from this plant, while 4'-hydroxy-3,7-dimethoxyflavone, vicenin-2 and kaempferol have been isolated from its leaves (Barbosa et al, 2008;Siraichi et al, 2013). There are reports of the antiinflammatory, anti-allergic, and anti-tumor properties of these compounds in the literature (Eda et al, 2002;Hirano et al, 2001;Seelinger et al, 2008).…”
Section: Phytochemical Studiesmentioning
confidence: 95%